PERENCANAAN PENCAHAYAAN BUATAN UNTUK RUANG MEMBATIK DI PERUSAHAAN BATIK PLENTONG YOGYAKARTA - Fauzi, Muhammad (Universitas Esa Unggul, 2017)
AbstractWith the increasing demand of Batik Plentong increasingly sharp so that the company is overwhelmed to serve the demand from domestic consumers and foreign consumers. On the other hand, batik plentong companies have an increase in workers therefore there is a need for comfort and safety factors for workers as applied to the law on the standardization of proper facilities. The process of batik using canting requires precision and high precision, thus requiring facilities or facilities that support the activity. Artificial lighting conditions in the batik